Eco-friendly, selective hydroxylation of C-7 aromatic compounds catalyzed by TS-1/H2O2 system under solvent-free solid-liquid-liquid-type triphase conditions - Mukherjee, P.; Bhaumik, Asim; Kumar, Rajiv (Industrial & Engineering Chemistry Research, 2007)
Direct ring hydroxylation of aromatics, namely, anisole, toluene, and benzylchloride, using TS-1 catalyst, a MFI-type titanium silicate molecular sieve, dilute H2O2 as oxidizing agent, and water as reaction medium, was investigated under solid-liquid-liquid (SLL)-type triphase conditions. The aim was to study the relative influence of commonly used organic solvents, under solid-liquid (SL)-type biphase reaction conditions, as compared to that of water, on the conversion and product selectivity. Under solvent-free triphase conditions, the ring hydroxylation of anisole, toluene, and benzylchloride leads to significant enhancement in the conversion, turn-over frequency, and para-selectivity. However, in the case of benzyl chloride, no ring hydroxylation took place under biphase conditions (using acetone as solvent) contrary to significant ring hydroxylation (ca. 60% H2O2 efficiency) under triphase aqueous medium conditions. The simple product recovery (phase separation of organic and aqueous layers) and use of water as reaction medium are other advantages. Since TS-1 is relatively hydrophobic, the reaction is hindered in the presence of organic solvents as they compete favorably with the substrate for diffusion inside the TS-1 channels. However, in the presence of water, the organic substrate competes favorably with water, leading to increased conversion and para-selectivity.

New microporous MOF material based on Zn(II)-polycarboxylate coordination polymer synthesized with the aid of 1,6-diaminohexane as template - Chandra, Debraj; Kasture, Mahesh W.; Bhaumik, Asim (Microporous and Mesoporous Materials, 2008)
A new microporous metal-organic framework (MOF) material ZBTEC-1 has been synthesized by designing infinite coordination polymer network formed between Zn(II) and 1,2,4,5-benzenetetracarboxylic acid (BTEC) under solvothermal conditions in the presence of 1,6-diaminohexane (DAH) as a single molecule template. Powder XRD data demonstrate that the ZBTEC-1 material has a new MOF structure. N-2 sorption studies indicated moderately good surface area (306 m(2) g(-1)) with large size micropores (average pore diameter ca. 0.7 nm) and very high pore volume (1.93 ccg(-1)). C-13 solid state MAS-NMR, FT-IR and UV-visible spectroscopic studies showed the presence of BTEC moieties in the framework. TEM and FE-SEM analysis indicated 30-60 nm diameter size microporous spherical particles for the ZBTEC-1 crystallites. This novel MOF material showed good hydrogen adsorption capacity at 77 K, indicating its potential application in hydrogen storage. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Coordination polymer; Metal-organic framework; Microporous material; porosity; Zinc complex

Incorporation of tin in different types of pores in SBA-15: synthesis, characterization and catalytic activity - Sasidharan, M.; Kiyozumi, Y.; Mal, N. K.; Paul, M.; Rajamohanan, P. R.; Bhaumik, Asim (Microporous and Mesoporous Materials, 2009)
Mesoporous Sn-SBA-15 has been synthesized by three different methods Such as conventional hydrothermal route, using cocatalyst NH4F and in the presence of organosilane precursor. All the materials are thoroughly characterized by powder X-ray diffraction (XRD), SEM. TEM. N-2 sorption and surface area measurements, diffuse-reflectance UV-visible and FTIR spectroscopy. TG-DTA and elemental analysis through ICP. Nitrogen adsorption data, XRD patterns, and TEM observations Suggests that the textural properties are retained during the isomorphous substitution of silicon by tin. ICP chemical analysis indicates that tin can be substituted in the range of S-l/S-n = 69-162. UV-visible spectra of samples synthesized by the cocatalytic approach exhibit unique absorption band at 213 nm characteristics of tin atom substituted in the smaller pores (2-3 nm) located inside the walls of mesopores. Further, an additional band at 224 nm can be assigned to Sri atoms located in the distorted tetrahedral position along the primary mesopores. In contrary, only one absorption band centered at 224 nm is observed for all the samples synthesized by conventional hydrothermal as well as in the presence of organosilane precursor. F-19 NMR spectra confirmed (no signal) the absence of occluded F- ions in the samples made with NH4F. Observed high catalytic activity in Baeyer-Villiger oxidation and Meerwin-Pondorf-Verly reduction under the liquid-phase conditions suggest the incorporation of a portion of tin in the smaller pores for the Sn-SBA-15 materials synthesized through cocatalyst method. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Baeyer-Villiger oxidation; catalysis; Functionalization of mesopores; Meerwin-Pondorf-Verly reduction; Sn-SBA-15

New organic-inorganic hybrid microporous organosilica having high metal ion adsorption capacity - Paul, Manidipa; Pal, Nabanita; Rajamohanan, P. R.; Rana, Bharat S.; Sinha, Anil K.; Bhaumik, Asim (Physical Chemistry Chemical Physics, 2010)
A new microporous organic-inorganic hybrid organosilica LHMM-2 containing a bis(propyliminomethyl)benzene moiety inside the framework has been synthesized hydrothermally without using any template or structure-directing agent. Powder XRD and TEM image analyses suggest a new disordered microporous structure with pores of dimension ca. 0.54 nm, and C-13 and Si-29 MAS NMR and spectroscopic results indicate the presence of bridging organic bis(propyliminomethyl) benzene moiety in this framework. TPD-NH3 results suggested that nearly 5 times as much bis(propyliminomethyl) benzene moiety is located inside the micropore walls (matrix) than in the surface of the pores. LHMM-2 shows very high adsorption capacity for metal cations like Fe3+, Cu2+ and Zn2+.

Nitrogen-rich porous covalent imine network (CIN) material as an efficient catalytic support for C-C coupling reactions - Bhunia, Manas K.; Das, Swapan K.; Pachfule, Pradip; Banerjee, Rahul; Bhaumik, Asim (Dalton Transactions, 2012)
In an effort to expand the realm of possibilities of nitrogen-rich porous materials that could be used in catalysis, herein we report the synthesis of a new highly nitrogen rich (ca. 45%) porous covalent imine network (CIN-1) material employing simple Schiff base chemistry and further grafting its surface with palladium. Pd-loaded CIN-1 support acts as a truly heterogeneous catalyst towards Suzuki C-C coupling reaction between aryl halides with arylboronic acids. High surface area and excellent accessibility of the catalytic sites make it very efficient for heterogeneous catalysis. The stability of the catalyst due to intimate contact between nitrogen-rich organic support and metal allows several reuses with only a minor loss in catalytic activity.

Purification of waste-generated biogas mixtures using covalent organic framework's high CO2 Selectivity - Paul, Ratul; Maibam, Ashakiran; Chatterjee, Rupak; Wang, Wenjing; Mukherjee, Triya; Das, Nitumani; Yellappa, Masapogu; Banerjee, Tanmay; Bhaumik, Asim; Venkata Mohan, S.; BabaRao, Ravichandar; Mondal, John (ACS APPLIED MATERIALS & INTERFACES, 2024)
Keywords: CAPTURE; CARBON-DIOXIDE; Efficiency; Energy; Hydrogen; STORAGE